Κοινωνική Ένταξη και Κοινωνικά Ευπαθείς Ομάδες - Παυλή-Κορρέ, Μαρία; Άννα Τσιμπουκλή; Μπαμπάλης, Θωμάς; Λευθεριώτου, Πιέρα; Γιαντσελίδου, Αγγελική (1ο Διεθνές Συνέδριο Διά βίου μάθηση, χώρος εργασίας και ανάπτυξη κοινωνικών δεξιοτήτων., 2024)
The present study focuses on specific socially vulnerable groups that face more risks for social and educational exclusion and stigma. These groups include Roma, people with mental health issues, prisoners and people who abuse drugs. The obstacles and motivation to participate in Lifelong Learning Programmes are discussed in addition with the availability of human and other resources, the state and media position on fighting stigma, the training of trainers and capacity building.